ANALISIS BUKU TEKS BAHASA ARAB MADRASAH ALIYAH KELAS XII TERBITAN KEMENTERIAN AGAMA DAN ERLANGGA - ., Mahfudz; Garancang, Sabaruddin; ., Haniah; Ima, Nur (Inspiratif Pendidikan, 2022)
This study aims to analyze and compare the quality of MA Arabic textbooks for class XII published by the Ministry of Religion and Erlangga, based on BSNP standards, namely: content aspects, presentation aspects, language aspects and graphic aspects. This research using qualitative content analysis to analyze textbooks Arabic. The steps taken are the formulation of the analysis objectives,Data grouping, assessment of the percentage component items of each subcomponents and aspects of feasibility and data analysis. The results of the study are Arabic textbooks published by the Ministry of Religion from the content feasibility component have a very good category, in terms of the presentation component in the good category, the linguistic component in the good category and the last component in terms of the graphic of this book has a very good quality. Arabic text book published by PT. Erlangga seen from the four components of the BSNP standard has very good quality, in terms of content, presentation, language and graphics. Comparison between the two books, the Arabic textbook published by PT. Erlangga is superior to Arabic textbooks published by the Ministry of Religion in terms of presentation and linguistic aspects. In terms of content and graphic aspects, the two books have a balanced quality.